Heterogeneous and self-organizing mineralization of bone matrix promoted by hydroxyapatite nanoparticles. Issue 44 (1st November 2017) - Campi, G.; Cristofaro, F.; Pani, G.; Fratini, M.; Pascucci, B.; Corsetto, P. A.; Weinhausen, B.; Cedola, A.; Rizzo, A. M.; Visai, L.; Rea, G.
Abstract : The mineralization process is crucial to the load-bearing characteristics of the bone extracellular matrix. Abstract : The mineralization process is crucial to the load-bearing characteristics of the bone extracellular matrix. In this work, we have studied the spatiotemporal dynamics of mineral deposition by human bone marrow mesenchymal stem cells differentiating toward osteoblasts promoted by the presence of exogenous hydroxyapatite nanoparticles. At the molecular level, the added nanoparticles positively modulated the expression of bone-specific markers and enhanced calcified matrix deposition during osteogenic differentiation. The nucleation, growth and spatial arrangement of newly deposited hydroxyapatite nanocrystals have been evaluated using scanning micro X-ray diffraction and scanning micro X-ray fluorescence. As leading results, we have found the emergence of a complex scenario where the spatial organization and temporal evolution of the process exhibit heterogeneous and self-organizing dynamics. At the same time the possibility of controlling the differentiation kinetics, through the addition of synthetic nanoparticles, paves the way to empower the generation of more structured bone scaffolds in tissue engineering and to design new drugs in regenerative medicine.